The effects of Alzheimer's disease related striatal pathologic changes on the fractional amplitude of low-frequency fluctuations. Issue 16 (9th December 2020) - Cakir, Yuksel
Abstract: This paper aims to correlate Alzheimer's disease (AD) related striatal pathologic changes with the fractional amplitude of low-frequency fluctuations (fALLF) in the blood oxygenation level-dependent (BOLD) signal in the resting state functional Magnetic Resonance Imaging (rs-fMRI). A dopamine modulated Izikhevich neuron model based network of striatum region is constructed. Balloon–Windkessel hemodynamic model is used to obtain BOLD signals. fALFF differences between two frequency bands (slow-5:0.01–0.027 Hz; slow-4:0.027–0.073 Hz) are investigated in the case of dopamine depletion, decrease in the synaptic connectivity and the input from cortical and thalamic region, assumed that they are the degenerations occurring in AD.